Design and Development of Smart Medical Devices: A Biomedical Perspective - Ashour, Hussein Awni; Mahdi, Hawra Aqeel; Khalid, Sanarya Waleed; Drsoon, Mariam Maan (American Journal of Biodiversity, 2025)
This essay on the design and development of smart medical devices in biomedicine comes in two interconnected parts. The first part narrates the experience of conceptualizing and developing a smart airbag assisted lying posture corrector from the perspective of a bio-dynamic design project. The second part reflects critically on the challenges and ethical issues involved in the development of smart medical devices, framed within the theoretical and methodological context of biomedical engineering. The film and animation projects screened at a global conference in 2018 and further public debates on the construction of white-collar-like digital immaterial labors explored bio-dynamism, somato-politics, and ubiquitously sedimented technocommodities. Especially inspired by the conference’s defense of an ’ongoing’ labor, this paper caught the opportunity of experiencing this bio-dynamic background to revisit the development of a smart medical device intended for home use. After the success of the filmic construction, and following requests from physiotherapists and healthcare consultants for sharing the device, a collaborative venture was eventually set up in 2010 with a medical equipment manufacturer in Beijing chosen by consulting with . From its inception, this project conceived the device as a set of airbags integrated into different types of upper torso garments to assist wearers in self-attaining a straight back and shoulders posture and in avoiding bending forward or sideways for a long period of time [1]. Five rounds of R&D were implemented, expanding from parchment paper scripting to prototype testing on twelve wearers over nine years.